Overview of systematic reviews on behavioral determinants of physical activity and healthy eating in schoolchildren - Anselmi, Giuliano Duarte; Barbosa, Adriana Aparecida de Oliveira [UNESP]; Ferrari, Gerson; Fernandes, Anna Christina Pinheiro; Araneda-Flores, Jacqueline; González, Danáe Arancibia; Pizarro-Quevedo, Tito (Springer Nature, 2025)
Childhood obesity and poor dietary habits represent significant public health challenges globally. Schools provide a crucial environment for interventions promoting physical activity and healthy eating behaviors due to their extensive reach and influential role in child development. This overview aims to synthesize evidence on the effectiveness of school-based interventions promoting physical activity and healthy eating behaviors among school-aged children, examining the role of behavior change techniques (BCTs) and behavioral determinants influencing their success. This study is an overview of systematic reviews and follows the Cochrane Handbook for Systematic Reviews of Interventions as well as the PRIOR (Preferred Reporting Items for Overviews of Reviews) statement. A literature searches until September 30, 2024, was performed in four electronic databases for this Overview: Cochrane database of systematic reviews, MEDLINE via PubMed, Epistemonikos, and PsycINFO. No language restrictions were imposed. Data were included and extracted from all systematic reviews evaluating interventions implemented in school settings targeting physical activity, healthy eating, or both, in children aged 6–11 years. Two reviewers independently screened the identified articles and extracted data related to the study characteristics, intervention components, behavioral outcomes (e.g., moderate-to-vigorous physical activity, dietary quality), cognitive outcomes (e.g., self-efficacy, knowledge, attitudes), and biological outcomes (e.g., BMI, waist circumference), classifying BCTs using standardized classifications whenever available. The AMSTAR-2 tool was used to evaluate the methodological quality of the included studies. Six systematic reviews, encompassing over 230,000 participants, were included. Multicomponent interventions combining physical activity, dietary education, cognitive strategies, and environmental modifications demonstrated consistent positive outcomes. Effective BCTs frequently identified included goal setting, self-monitoring, restructuring the physical environment, and providing feedback on behavior, especially via digital platforms. While significant improvements were consistently noted in behavioral outcomes such as increased physical activity and improved dietary habits, evidence regarding cognitive and biological outcomes like BMI reduction was moderate yet favorable. Methodological quality varied, with most reviews rated critically low, except for one high-quality Cochrane review. School-based interventions integrating multiple BCTs, particularly goal setting, self-monitoring, feedback, and environmental restructuring, are effective in promoting physical activity and healthy eating among school-aged children. Future interventions should emphasize long-term sustainability, technological integration, and address existing methodological limitations to enhance effectiveness and generalizability.Systematic review registration Registered in PROSPERO CRD42024587296 on September 16, 2024.